The Pengaruh Latihan Aerobik : Range Of Motion Terhadap Fungsi Kognitif Lanjut Usia dengan Demensia-Alzeimer - Anggraeni Putri, Laila; Rahmi, Upik; Salasa, Sehabudin (Universitas Hamzanwadi, 2025)
The purpose of this study was to analyze the effect of aerobic range of motion exercises on cognitive function of elderly people with dementia-alzeimer. The method in this study is experimental with a pretest and posttest control group design, the researcher involved 28 elderly respondents who were in the senjarawi social home, the respondents in this study consisted of 19 female respondents and 9 male respondents. Measurements were taken using the mini mental state examination (MMSE). The results of this study showed a significant increase between pretest and posttest (p < 0.000), in this study showed that there was a significant difference, this change indicated an improvement in cognitive function in some respondents, characterized by an increase in the number of individuals in the mild category and a decrease in the moderate category after the intervention, this finding can be an early indication that the intervention provided has the potential to have a positive impact on the cognitive function of respondents. Conclusion exercise training (ROM) contributes significantly in improving the cognitive function of elderly with mild to moderate dementia, this affects time recall, short-term memory, comprehension and execution of verbal commands.